Obésité, facteurs socio-démographiques et indicateurs de santé chez les personnes âgées à Marseille - Enguerran Macia; Nicole Chapuis-Lucciani; Gilles Boëtsch (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The purpose of this study is threefold: (1) to determine whether the socio-demographic factors of age, level of education and marital status have the same impact on obesity in women and in men aged 60 years and above; (2) to evaluate the associations between obesity on the one hand and self-rated health, physical incapacities and self-esteem on the other; (3) to test the mediatory potential of cardio-vascular diseases and diabetes on the relationship between obesity and self-rated health. For this, 400 persons aged from 60 to 92 years, living in Marseille, were questioned. These individual encounters included anthropometric measurement, and an interview carried out with the aid of a questionnaire (average duration: 1h30). The prevalence of obesity in our population sample is 17%, a rate comparable to the whole of this age group in the French population. Our analyses show that the correlates of obesity are very different between older women and men. For the men, only marital status is significantly associated with obesity while for the women, age, education level, self-rated health and physical incapacities are associated with obesity. Finally we have shown that the relation between obesity and self-rated health (for the women) is an indirect association affected by cardio-vascular diseases.